Produksi Hidrogen Menggunakan Teknik Elektrolisis Air Dengan Variabel Kuat Arus: The Production Of Hydrogen Gas Employing Water Electrolysis With Electrical Current Variabels - Messiah Charity Sangian; Glanny Martial C Mangindaan; Hanny Frans Sangian (Jurnal Teknik Elektro dan Komputer, 2023)
Abstract — This work aimed to produce HHO gas using water electrolysis with an electrical current ranging from 10 A to 100 A, and the area of electrode plates was 2×18×30×30 cm2. The electrolysis apparatus is constructed in an acrylic container which is composed of 9 plates of positive electrode followed by 9 plates of the negative electrode and separated by a diaphragm. The box filled with electrolyte liquid was at 25 Liters and each electrode was connected to a power supply whereby the current and voltage could be altered. The first study was at producing HHO gas using pure water without employing a catalyst and the electrical current was changed instead. Furthermore, the application of catalyst as much as 200-400 grams. It was found that the highest volume of HHO gas was produced with a current of 70 Amperes with a mass of 400 grams catalyst, amounting to 1.300 mL in 113 seconds while the volume of HHO gas was at current of 10 Amperes without catalyst, amounting to 200 mL in 139 seconds. Key words — Water electrolysis; HHO gas; electric current; catalyst.   Abstrak — Tujuan dari penelitian ini adalah untuk menghasilkan gas HHO menggunakan elektrolisis air dengan arus listrik mulai dari 10-100 Ampere dengan luas pelat elektroda 2×18×30×30 cm2. Alat elektrolisis dirancang dalam satu wadah berbahan akrilik yang tersusun atas 9 pelat elektroda positif dan 9 pelat elektroda negatif dan dipisahkan oleh diafragma. Larutan elektrolit sebanyak 25 Liter dimasukkan ke dalam wadah dan setiap elektroda dihubungkan ke power supply sehingga arus dan tegangan dapat diubah. Percobaan awal adalah produksi gas HHO menggunakan air murni tanpa katalis dengan variasi arus listrik. Selanjutnya dilakukan penambahan katalis sebanyak 200-400 gram. Ditemukan bahwa volume gas HHO terbanyak dihasilkan oleh kuat arus 70 Ampere dengan massa katalis 400 gram sejumlah 1.300 mL dalam 113 detik sedangkan untuk volume gas HHO terendah terdapat di kuat arus 10 A tanpa katalis sebesar 200 mL pada 139 detik. Kata kunci —  Elektrolisis Air, Gas HHO, Arus Listrik, Katalis.